Dendrite corrosion of 316L stainless steel weld joint in NaCl–MgCl2 molten salt loop - Yafei Wang; Cody Falconer; Adrien Couet (npj Materials Degradation)
Abstract One major concern in molten salt reactor (MSR) is structural material corrosion. In this study, the corrosion performance of 316L stainless steel weld joint in NaCl–MgCl2 eutectic molten salt loop was studied and compared with its base metal. The corrosion of 316L stainless steel in a molten salt loop appears to create voids. The created voids appear densely in base metal while spread discretely as dendritic structures in the weld joint.